2017
DOI: 10.1097/fpc.0000000000000268
|View full text |Cite
|
Sign up to set email alerts
|

Influence of common polymorphisms in the SLC5A2 gene on metabolic traits in subjects at increased risk of diabetes and on response to empagliflozin treatment in patients with diabetes

Abstract: Common genetic variants in the SLC5A2 gene neither affects diabetes-related metabolic traits nor have a clinically relevant impact on response to treatment with the SGLT2 inhibitor empagliflozin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 26 publications
2
32
3
2
Order By: Relevance
“…Therefore, we analysed whether common genetic variation in the human SGLT2 gene SLC5A2 associates with fasting and glucose-suppressed circulating glucagon concentrations. We analysed the four tagging SNPs that were recently tested in a larger study population (N = 2,229) from our TÜF study for association with glycemic traits, insulin sensitivity, insulin secretion, blood pressure, and glomerular filtration [9]. In this earlier study, we found nominal associations of SNP rs3116150 with fasting glycemia, glucose excursions during the 5-point OGTT (AUC glucose), and systolic blood pressure [9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we analysed whether common genetic variation in the human SGLT2 gene SLC5A2 associates with fasting and glucose-suppressed circulating glucagon concentrations. We analysed the four tagging SNPs that were recently tested in a larger study population (N = 2,229) from our TÜF study for association with glycemic traits, insulin sensitivity, insulin secretion, blood pressure, and glomerular filtration [9]. In this earlier study, we found nominal associations of SNP rs3116150 with fasting glycemia, glucose excursions during the 5-point OGTT (AUC glucose), and systolic blood pressure [9].…”
Section: Discussionmentioning
confidence: 99%
“…We analysed the four tagging SNPs that were recently tested in a larger study population (N = 2,229) from our TÜF study for association with glycemic traits, insulin sensitivity, insulin secretion, blood pressure, and glomerular filtration [9]. In this earlier study, we found nominal associations of SNP rs3116150 with fasting glycemia, glucose excursions during the 5-point OGTT (AUC glucose), and systolic blood pressure [9]. Three of our four SNPs (rs3116150, rs3813008, rs9934336) were also studied by Enigk et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations